Mnemonic utilization in stroke education: FAST and BEFAST adoption by certified comprehensive stroke centers - Hogge, Christopher; Goldstein, Larry B.; Aroor, Sushanth R. (Frontiers in Neurology, 2024)
Introduction Symptom recognition and timely access to treatment are critical components of acute stroke care systems. Two mnemonics widely used in public educational campaigns for recognizing stroke symptoms include FAST (Face-Arm-Speech-Time) and BEFAST (Balance-Eyes-Face-Arm Speech-Time). The FAST mnemonic can miss up to 14% of strokes. BEFAST includes common posterior circulation stroke symptoms and has been implemented by several Comprehensive Stroke Centers (CSCs). Methods We sought to analyze the pattern of public educational materials available on the websites of US CSCs. The Joint Commission (JC) quality check website compiles a list containing the names and locations of the country’s 217 JC-certified CSCs, which was downloaded in August, 2022. Each CSC’s website was searched for educational material containing FAST and BEFAST mnemonics for stroke symptom recognition. Results The FAST mnemonic was listed by 35% of CSCs, the BEFAST by 58%, with 7% listing no specific mnemonic. The highest portion of CSCs using BEFAST was in western (65%) and southeastern (63%) states. The highest percentage of CSCs with no listed mnemonic were in the northeastern (14%) and southeastern (13%) states. Conclusion Consistency is critical in shaping public health education related to stroke symptoms recognition. Our study suggests further effort is needed to unify the public messaging on stroke recognition.